Identification of HMGA2 as a predictive biomarker of response to bintrafusp alfa in a phase 1 trial in patients with advanced triple-negative breast cancer - Spira, Alexander; Awada, Ahmad; Isambert, Nicolas; Lorente, David; Penel, Nicolas; Zhang, Yue; Ojalvo, Laureen S.; Hicking, Christine; Rolfe, P. Alexander; Ihling, Christian; Dussault, Isabelle; Locke, George; et al. (Frontiers in Oncology, 2022)
Background: We report the clinical activity, safety, and identification of a predictive biomarker for bintrafusp alfa, a first-in-class bifunctional fusion protein composed of the extracellular domain of TGFβRII (a TGF-β “trap”) fused to a human IgG1 mAb blocking PD-L1, in patients with advanced triple-negative breast cancer (TNBC). Methods: In this expansion cohort of a global phase 1 study, patients with pretreated, advanced TNBC received bintrafusp alfa 1200 mg every 2 weeks intravenously until disease progression, unacceptable toxicity, or withdrawal. The primary objective was confirmed best overall response by RECIST 1.1 assessed per independent review committee (IRC). Results: As of May 15, 2020, 33 patients had received bintrafusp alfa, for a median of 6.0 (range, 2.0-48.1) weeks. The objective response rate was 9.1% (95% CI, 1.9-24.3) by IRC and investigator assessment. The median progression-free survival per IRC was 1.3 (95% CI, 1.2-1.4) months, and median overall survival was 7.7 (95% CI, 2.1-10.9) months. Twenty-five patients (75.8%) experienced treatment-related adverse events (TRAEs). Grade 3 TRAEs occurred in 5 patients (15.2%); no patients had a grade 4 TRAE. There was 1 treatment-related death (dyspnea, hemolysis, and thrombocytopenia in a patient with extensive disease at trial entry). Responses occurred independently of PD-L1 expression, and tumor RNAseq data identified HMGA2 as a potential biomarker of response. Conclusions: Bintrafusp alfa showed clinical activity and manageable safety in patients with heavily pretreated advanced TNBC. HMGA2 was identified as a potential predictive biomarker of response. ClinicalTrials.gov identifier: NCT02517398